Solusi Model Pendidikan Islam Bagi Anak Berkebutuhan Khusus di Sekolah Inklusif - Nuurtanty, Oktavia; Muadin, Akhmad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
This research explains the study of Islamic education for children with special needs who study in inclusive schools. Inclusive schools are schools that provide inclusive education where the education system provides opportunities for students with special needs to receive educational services together with students in general. The method or approach used in this study is library research. With this method, researchers collect, read, analyze, record and process information related to the research variables of this paper. The results of this research show, Islamic education is the right of every Muslim without any reason. Islamic education has an obligation to lead students to happiness in this world and the hereafter. Children with special needs also have the same rights as God's servants on earth, they have potential that must be developed so that they can benefit themselves and the wider community. Islamic education in inclusive schools can be realized well if there is strong synergy from every supporting element, from the government, school management, teachers, parents and the surrounding community, as well as the students.